The Role of Risk Management in Overcoming Human Resource Challenges at the TNI Supply Agency in the Digitalization Era - Dony Antariksa, Susilo Negoro; Pujiati, Herni (Dinasti International Journal of Digital Business Management, 2025)
The Indonesian National Armed Forces Supply Agency (Babek TNI) plays a strategic role in supporting TNI operations through centralized and integrated procurement of goods and services. In the digitalization era, Babek TNI faces various challenges in managing Human Resources (HR), including technology adaptation, information security, and personnel competency improvement. This study aims to analyze the role of risk management in addressing these challenges using a qualitative approach with a literature review method. Data were obtained from various academic sources, relevant policies, and reports on risk management implementation in the military sector. The analysis results indicate that effective risk management implementation can minimize the negative impacts of risks, improve operational efficiency, and ensure the readiness of Babek TNI’s HR in supporting its primary tasks. This study also finds that integrating digital technology with a risk management framework can strengthen the HR management process. These findings provide practical recommendations for Babek TNI to develop adaptive risk management strategies, including continuous training, technology risk monitoring, and data-driven policy reinforcement. Thus, risk management plays a significant role in addressing HR challenges within Babek TNI in the digitalization era.